Action modes of the immune modulating activities of crude mushroom polysaccharide from Phallus atrovolvatus. (July 2020) - Chaiyama, Varaporn; Keawsompong, Suttipun; LeBlanc, Jean Guy; de Moreno de LeBlanc, Alejandra; Chatel, Jean-Marc; Chanput, Wasaporn
Abstract: Phallus atrovolvatus is a wild edible mushroom which is recently being cultivated in Thailand. It contains a remarkable amount of β-(1, 3–1, 6)-glucan, a compound known for its immune modulating properties. Crude mushroom polysaccharide (CMP) was obtained from the fruiting body of P. atrovolvatus using boiling water extraction, followed by overnight ethanol cold precipitation. CMP is composed of approximately 50% β-glucan, α-glucan, proteins, ash and other non-digestible polysaccharide. In this study, we evaluated the immune modulating activities of CMP using in vitro and in vivo models. In vitro, CMP was treated with the transfected NF-κB reporter-HEK 293 recombinant cell line, the results showed no cytotoxicity up to 500 μg/mL, and CMP treatments exhibited a higher % NF-κB luciferase expression. DiNitroBenzene Sulfonic acid (DNBS)-induced colitis mice model was used to elucidate the effects of CMP in vivo . Colitis severity was assessed using body weight trend, macroscopic scores and histological scores. Myeloperoxidase (MPO) activity and cytokine production were determined from the colon tissue and spleen, respectively. The results showed that oral consumption of 50 μg CMP/mouse/day could significantly decrease MPO activity and reduce the secretion of TNF-α, IL-6, IL-10, and IL-17A cytokines. To our knowledge, this study shows the first time the report of immune modulating activities of Phallus atrovolvatus Thai strain. The results lead to the conclusion that CMP provides two modes of actions: i) stimulating the NF-κB pathway and ii) acting as an anti-inflammatory that can protect mice against induced colitis. Highlights: Crude mushroom polysaccharide from Phallus atrovovatus exhibited immune stimulating activity through the NF-κB pathway. Anti-inflammatory activity of Phallus atrovovatus is derived from reduction of pro-inflammatory cytokine production in spleen. Crude mushroom polysaccharide from Phallus atrovovatus was not toxic to HEK 293 cells.